The relationship between women principal instructional leadership practices, teacher organizational commitment and teacher professional community practice in secondary schools in Kuala Lumpur / Farhana Mannan - Farhana , Mannan (2017)
With the implementation of the Malaysia Education Blueprint (2013-2025), the role of principal as an instructional leader has been widely debated in the education system. This debate is further extended to Malaysian women principals as instructional leaders on various factors influencing school outcomes. Therefore, this study aims to identify and analyze the relationship among women principal instructional leadership practices, teacher organizational commitment, teacher professional community practice and teacher demographic variables. The non-experimental quantitative study was conducted using a survey containing information on teacher demographic variables and 74 items related to women principal instructional leadership practice, teacher organizational commitment, and teacher professional community practice. Questionnaires were distributed to teachers in 39 Federal Territory of Kuala Lumpur public secondary schools that were headed by women principals. A Total of 357 questionnaires were randomly selected as the final sample of analyses. Thereafter, data were analyzed with Statistical Packages for the Social Sciences and Analysis of Moment Structures. According to demographics of respondents, the majority (81.2%) were female and rest (18.8%) were male teachers, while most teachers (73.1%) were Malays, followed by Chinese (18.0%) and Indians (10.9%). Most of the respondents were aged between 31 and 40 years. Additionally, the majority of teachers (46.8%) had 10 years of teaching experience, with most of them (84.0%) have a bachelor’s degree. In addition, the main group of respondents (86.8%) had worked under their respective principals for less than 5 years. The researcher used numerical rating-scale and found a normal distribution of the data. The data were subjected to descriptive and inferential analysis. The findings show that school teachers rated their women principals as having moderate level of instructional leadership practices. The teachers rated themselves as having moderate level of teacher organizational commitment but a high level of teacher professional community practice. Pearson product moment correlation shows a positive and significant relationship among women principal instructional leadership practices, teacher professional community practice and teacher organizational commitment. According to multiple regression analysis, only developing a positive school learning climate is a significant predicting dimension of teacher organizational commitment. Teacher professional community practice is a partial mediator between the relationship of women principal instructional leadership practices and teacher organizational commitment. The demographic variables of teachers such as gender, age, race, teaching experience, education level and years of service with respective principals act as a moderator to the relationship between women principal instructional leadership practices and teacher organizational commitment. The model fitness indices reflect that the data collected from the respondents fit into the proposed model. Therefore, this study reveals that women principals have the potential to enhance professional community practice in schools but they need a well-organized training to enhance their instructional leadership practices and to uplift the level of teacher organizational commitment. Besides, policy makers can take some initiatives to apply this model for more effective and efficient teaching and learning processes in Malaysian schools.